A Māori concept in a Pākehā world: biculturalism in health and physical education in the New Zealand curriculum. Issue 3 (1st September 2020) - Meier, Caroline; Culpan, Ian
ABSTRACT: This paper provides insights into political battles associated with the attempted introduction of a postcolonial bicultural dimension to the 'Health Physical Education in the New Zealand Curriculum' (NZHPE). Limited attention has been given to the gestation period of four years between the submission, release of the draft and the final publication of the NZHPE (Ministry of Education, 1999 ). This paper offers an analysis of the process of producing the curriculum from a postcolonial bicultural perspective. It brings to light the impact of neoliberal forces on the NZHPE and thus, on critical elements within the New Zealand (NZ) education system. Furthermore, it investigates the extent to which Māori (indigenous people in NZ) knowledge is accepted within a NZ neoliberal context. The paper concludes that through the introduction of the Māori concept Hauora into the NZHPE, Māori culture has gotten 'caught in the crossfire' between numerous scholars and advocates of neoliberalism. This has entailed the risk of reducing Māori culture to a means to an end – i.e. it being appropriated by Pākehā (people of European descent) for political and ideological interests. This could eventually cause considerable damage to the culture and thus, the relationship between Māori and Pākehā.